2022
DOI: 10.3390/jcm11051300
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Treatment with Adjuvant Chemotherapy for Ovarian Cancer on Disorders in the Urinary System and Quality of Life in Women

Abstract: Ovarian cancer is the fourth-most-common cause of death among all malignant cancers in women in Poland. This study aimed to compare the functioning of the urinary system and quality of life in women in the 12-month period following the completion of surgery or adjuvant treatment for ovarian cancer, with patients who underwent a hysterectomy for non-oncological reasons (control group). The study group consisted of 50 patients diagnosed with stage I–III ovarian cancer. Among 38 patients with type II ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Fourthly, this is one of very few studies from Poland regarding sexual function – the latest was recently published by Opławski et al . showing (by using satisfaction with life scale and sexual satisfaction scale) a deterioration of sexual function in ovarian cancer patients that did not markedly improve over time after surgery or surgery plus chemotherapy [ 14 ]. That paper, however, did not assess couple’s sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, this is one of very few studies from Poland regarding sexual function – the latest was recently published by Opławski et al . showing (by using satisfaction with life scale and sexual satisfaction scale) a deterioration of sexual function in ovarian cancer patients that did not markedly improve over time after surgery or surgery plus chemotherapy [ 14 ]. That paper, however, did not assess couple’s sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, we found a significant rate (27%) of acute urinary dysfunction among patients with cancer undergoing acute inpatient rehabilitation. Previous studies on urinary dysfunction in patients with cancer reported a variety of urinary dysfunction types affecting the quality of life [9][10][11][12]. These studies concentrated on patients with specific cancer types such as prostate, colorectal, endometrial, and ovarian cancer [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on urinary dysfunction in patients with cancer reported a variety of urinary dysfunction types affecting the quality of life [9][10][11][12]. These studies concentrated on patients with specific cancer types such as prostate, colorectal, endometrial, and ovarian cancer [9][10][11][12]. Other studies have described urinary dysfunction primarily in patients undergoing inpatient rehabilitation for strokes [19], brain disorders [20][21], spinal cord disorders [22][23][24], and other neurological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are classified according to those who have achieved a complete response (CR), a partial response (PR), a stable disease (SD) state, and progression (PR) [ 10 , 11 , 12 , 13 ]. In a previous study, we conducted a clinical and molecular characterization of the same ovarian cancer patients in the context of treatment efficacy and chemotherapy resistance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%